2020
DOI: 10.1111/vec.12942
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the induction of emesis with apomorphine as treatment for gastric foreign bodies in dogs (2010‐2014): 61 cases

Abstract: Objective To determine the success rate and complications associated with inducing emesis in dogs that have ingested foreign material. Design Retrospective case series, 2010–2014. Setting Private practice and referral center. Animals Sixty‐one client‐owned dogs that had emesis induced for the treatment of ingestion of foreign material. Interventions None. Measurements and Main Results Emesis was successfully induced in 59 of 61 (97%) dogs administered an emetic. Of those 59 dogs, 46 (78%) produced the foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(29 reference statements)
0
7
0
Order By: Relevance
“… 14 While recent studies suggest aspiration pneumonia is a rare complication of emesis induction in dogs, emetic agents used in dogs do not cause sedation as profound as dexmedetomidine does in cats. 15 , 16 However, the findings of this case series also suggest that orally administered dexmedetomidine can be successfully reversed with IM atipamezole, as all cats recovered uneventfully once reversed. Although profound sedation was observed in this study, the study by Santos et al, 10 investigating 20 µg/kg dexmedetomidine administered orally, reported much less sedation.…”
Section: Discussionmentioning
confidence: 67%
“… 14 While recent studies suggest aspiration pneumonia is a rare complication of emesis induction in dogs, emetic agents used in dogs do not cause sedation as profound as dexmedetomidine does in cats. 15 , 16 However, the findings of this case series also suggest that orally administered dexmedetomidine can be successfully reversed with IM atipamezole, as all cats recovered uneventfully once reversed. Although profound sedation was observed in this study, the study by Santos et al, 10 investigating 20 µg/kg dexmedetomidine administered orally, reported much less sedation.…”
Section: Discussionmentioning
confidence: 67%
“… 18 Considerations regarding management of G‐bFBs also differ from other foreign bodies because bones are potentially digestible, compared to other materials ingested by dogs, such as fabric, plastic, and rocks. 17 Although members of the order Carnivora, dogs are omnivorous; their wild relatives consume both prey and carrion, 19 and would be expected to ingest and digest bones. Therefore, another approach to the management of G‐bFBs is to leave them in situ for digestion.…”
Section: Discussionmentioning
confidence: 99%
“…When gastric foreign body removal is indicated, this can be attempted through induction of emesis, 17 endoscopy, or surgery. Bone foreign bodies resolved by emesis were not included in this study, and while induction of emesis, for example with apomorphine, might be a valuable approach for soft materials such as socks or tampons, it is less appropriate for resolution of sharp objects, 17 and is not a common approach with bone foreign bodies 18 . Considerations regarding management of G‐bFBs also differ from other foreign bodies because bones are potentially digestible, compared to other materials ingested by dogs, such as fabric, plastic, and rocks 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I ngestion of toxins or foreign material is a common clinical presentation for dogs, with numerous studies [1][2][3][4][5][6][7][8] emphasizing the importance of prompt gastrointestinal decontamination. Induction of emesis with apomorphine is a highly effective option in dogs.…”
mentioning
confidence: 99%